Osseous hemangioma of nasal cavity - Patil, Meena; Jagdale, Kunda; Joshi, Sujit (International Journal of Advances in Medicine, 2017)
Osseous hemangiomas are uncommon, constituting less than 1% of all osseous neoplasms. Most commonly affects maxilla, mandible & nasal bones. We report a case of an osseous hemangioma of nasal cavity. Cavernous hemangioma of the nose is a rare lesion and is one of the differential diagnosis of an intranasal bleeding mass.